Efektifitas Metode Jigsaw Terhadap Hasil Belajar Siswa Dalam Matapelajaran Matematika Tema Bilangan - Mubin, Minahul; Haryanto, Farizal (Jurnal Syntax Fusion, 2022)
Education has a very important role for continuity in the development of a nation. As a human being who is educated and has skills in a field. The research method used in this study is the Classroom Action Research Method using a qualitative approach. Classroom action with a qualitative approach is a method used by teachers in order to improve student learning processes and outcomes. Mathematics lesson on number material by applying the jigsaw cooperative learning model, results in a satisfactory increase in the mastery of number material, students more easily accept the material presented by the teacher compared to the previous learning method which relatively students get bored easily in learning, using the cooperative learning model jigsaw which makes students more active in learning, and with expert groups it is easier for students to understand lessons with joint discussions. This study aims to determine whether there are differences in the use of the Jigsaw cooperative method on learning outcomes and students' learning process skills in Mathematics subject matter of Numbers in grade IV. Based on the results of the analysis of process data and student learning outcomes data. so that it can be said that the use of the Jigsaw Cooperative learning method is effectively used on learning outcomes and skills of fourth grade students on Numbers.